T7. UPDATED INDIVIDUAL PARTICIPANT DATA META-ANALYSIS CONFIRMS LOWER LEVELS OF THE GLIAL MARKER TSPO IN PSYCHOSIS PATIENTS - Plavén-Sigray, Pontus; Matheson, Granville; Coughlin, Jennifer; Hafizi, Sina; Laurikainen, Heikki; Ottoy, Julie; de’Picker, Livia; Rusjan, Pablo; Hietala, Jarmo; Howes, Oliver; Mizrahi, Romina; Morrens, Manuel; et al. (SCHIZOPHRENIA BULLETIN, 2020)
BackgroundTreatment targeting the immune system is a promising new approach in schizophrenia. In search for tools for stratification and treatment monitoring, much effort has been invested in the use of positron emission tomography (PET) and radioligands binding to a glial marker, the 18 kDa translocator protein (TSPO). We previously demonstrated lower TSPO in psychosis patients in an individual participant data (IPD) meta-analysis of studies using second generation TSPO radioligands (Plavén-Sigray et al., 2018). Subsequently, a summary-statistics meta-analysis, including one newly published study, showed no difference (Marques et al., 2019). Here, the aim was to repeat the IPD analysis including this new sample, and an additional unpublished dataset in first episode psychosis patients. The primary objective was to re-evaluate the hypotheses of 1) higher or 2) lower or 3) no difference in radioligand binding between patients and healthy control subjects. Secondary objectives were to assess the effects of antipsychotic medication on TSPO binding, as well as relationships between TSPO binding and disease duration and symptom measures.MethodsIndividual participant data were obtained from PET studies that 1) used a second generation TSPO radioligand, 2) reported distribution volume (VT) values in brain in patients with psychosis as compared to healthy controls, and 3) reported TSPO affinity type of all participants. The outcome measure was VT in frontal cortex (FC), temporal cortex (TC) and hippocampus (HIP). Bayes factors (BF) were applied to examine the relative support for higher, lower, or no-change of TSPO levels in patients compared to healthy controls.ResultsIndividual participant data from seven studies were included, amounting to 99 patients with first-episode psychosis or schizophrenia and 109 healthy control subjects. In all regions investigated, BF showed moderate to strong support (BF > 5) for lower VT in patients as compared to no difference, and strong support (BF > 10) for lower VT compared to higher VT in patients. Mean patient-control differences in standardized VT values were -0.41 for FC (95%CI -0.67 to -0.15, p = 0.0022), -0.38 for TC (95%CI -0.64 to -0.12, p = 0.0048) and -0.53 for HIP (95% CI -0.79 to -0.27, p = 0.0001). The mean change in standardized VT due to medication was 0.10 for FC (CI95% -0.10 to 0.30, p = 0.615), -0.08 for TC (CI95% -0.32 to 0.48, p = 0.666) and 0.08 for HIP (CI95% -0.46 to 0.30, p = 0.682). No association was observed between VT and disease duration or symptom levels (all p > 0.526).DiscussionIn this updated IPD meta-analysis including two new datasets, we found moderate to strong support for lower TSPO in psychosis patients compared to control subjects. In vitro data has shown a lack of correspondence between TSPO and pro-inflammatory activation, also recently confirmed in a post-mortem study in schizophrenia. Hence, based on the present results no firm conclusions can be made regarding the pro- versus anti-inflammatory status of glial cells in psychosis patients. Additional work is needed to understand the biological relevance of the observed lower TSPO in patients.